(untitled) (International Journal of Engineering and Computer Science, 2018)
Technological changes based on the art of optical signal processing technologies and devices their limitations and thus there is increased focus on technologies that use photons. There are vast opportunities to carrying information in the field of fiber optics for communication purpose. Basically there are two types of fiber optics cables are used i.e. step graded and graded index. Fiber-optic networks have been used for decades to transmit large volumes of traffic across the country. The economics of fiber networks have only recently allowed for connecting the fiber directly to the home, creating a fiber-to-the-home (FTTH) network. FOSAPP objectives to develop a high-speed fiber optic data link, future prospects such as FTT/FISL and HFC are the challenging opportunities in the status of fiber optics in the counter’s. Fiber-optic networks have been used for decades to transmit large volumes of traffic across the country. The economics of fiber networks have only recently allowed for connecting the fiber directly to the home, creating a fiber-to-the-home (FTTH) network.